(untitled) (Patan Pragya, 2021)
This paper is based on problems and challenges of foreign labour migration and the main aim of this paper is to identity the problems and challenges faced by migrant workers in the destination countries, and is based on five different manpower agencies. Information was collected through 255 respondents and respondent’s household’s information and descriptive and cross sectional research design and sample selection has been based on purposive method. About 37.3 percent foreign labour migrants want to go Malaysia and highest i.e. 29.4 percent respondents want to go foreign labour work by cause of poverty and 23.5 percent respondents by cause of unemployment. More than 90 percent respondents do not have any knowledge about right of foreign labour migrants. Total 163 respondents had returned from foreign labour migration; the highest 36.2 percent respondents are returned back from Malaysia. More than 55 percent foreign labour migrants stayed in foreign employment for 2-4 year and 35 percent returned migrants engaged in factory labour and 36 percent foreign labour returned migrants worked 12 hours. The highest i.e. 60.8 percent returned foreign labour migrants were sick of frequent fever and 58.8 percent foreign labour returned migrants had their treatment charge paid by their companies. Lack of information about the adequate the destination countries, poverty, unemployment, manpower agencies or agents’ exploitation, discrepancy in wages before and after departure, working condition and situation in the destination countries, language, environment, out off that work permit problems are the major problems in both origin and destination place. To promote the rights of migrant’s worker is major issue in present time. Foreign labour migration sending the large amount of remittance of Nepal, but they have not been able to utilize in productive sectors.